1995
DOI: 10.1007/bf02310354
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of ceftazidime in febrile neutropenic patients with acute myeloid leukemia

Abstract: Twelve febrile patients with severe neutropenia, who had undergone aggressive chemotherapy for acute myeloid leukemia, were treated empirically with a continuous infusion of ceftazidime 100 mg/kg/day after a 500 mg loading dose, in order to study the pharmacokinetics of ceftazidime after continuous infusion and to examine the clinical applicability of continuous infusion in this patient population. Three patients had a slight decrease in renal function. All patients attained a steady-state ceftazidime serum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 18 publications
5
27
0
1
Order By: Relevance
“…Ceftazidime's pharmacokinetic parameters are in agreement with other authors' findings showing that an enlarged volume of distribution and/or increased renal clearance may occur in patients with hematological malignancies (6,14). Consistently, in order to maintain an appropriate t Ͼ MIC, higher intermittent dosages were advocated (14).…”
supporting
confidence: 88%
“…Ceftazidime's pharmacokinetic parameters are in agreement with other authors' findings showing that an enlarged volume of distribution and/or increased renal clearance may occur in patients with hematological malignancies (6,14). Consistently, in order to maintain an appropriate t Ͼ MIC, higher intermittent dosages were advocated (14).…”
supporting
confidence: 88%
“…Although the concept of continuous infusion is supported by ␤-lactam pharmacodynamics (8,27), suggesting that maximization of the fT Ͼ MIC should be a critical factor for a positive outcome, clinical studies supporting this are limited. The majority of supporting data have been derived from either in vitro or animal models of infection, which demonstrated equivalent or improved end points with continuous infusion (2,25,26), or from small case reports, retrospective studies, or prospective observational trials (1,9,10,11,14,20,22,28). In one randomized, comparative trial of 100 febrile neutropenic patients, intermittent carbenicillin infusion plus continuous cefamandole infusion achieved a greater effectiveness than intermittent carbenicillin infusion plus intermittent cefamandole infusion in the subgroup of patients with agranulocytosis (absolute neutrophil count, Ͻ100/mm 3 ) (4).…”
Section: Discussionmentioning
confidence: 99%
“…The superior effectiveness of continuous infusion over intermittent infusion has been demonstrated for ␤-lactams in animal studies (2,8,25,26); however, clinical data comparing continuous and intermittent infusions are limited and consist primarily of data from small studies and case reports (1,3,6,9,10,11,19,22,28). In most of these studies, similar clinical and microbiological outcomes have been observed for the two administration techniques, but none of the studies have had sufficient power to conclude noninferiority.…”
mentioning
confidence: 99%
“…Many clinical studies assessing continuous and prolonged infusion were conducted through the 1990s, but only a few were clinical randomized controlled trials, mostly addressing only pharmacologic endpoints (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and only two reported patients' outcomes. In 1979, Bodey and colleagues found that an antibiotic combination containing continuous-infusion cefamandole achieved the greatest cure rates in 490 febrile episodes with neutropenia (48).…”
Section: Historical Reviewmentioning
confidence: 99%